Pengembangan Sistem Informasi Manajemen Konten Digital untuk UMKM (Studi Kasus: Kota Gorontalo) - Amuda, Putra Anshori Arta; Koniyo, Moh. Hidayat; Dwinanto, Arif; Yusuf, Rampi; Dangkua, Eka Vickraien (Universitas Negeri Gorontalo, 2025)
ABSTRACT. Micro, Small, and Medium Enterprises (MSMEs) in Gorontalo City have adopted social media for marketing purposes; however, its utilization remains suboptimal due to time constraints and a lack of strategic understanding regarding digital content management. Preliminary surveys indicate that many MSMEs lack a structured posting schedule and face difficulties in objectively measuring promotional effectiveness. As a practical solution, this research designs and develops a web-based Digital Content Management Information System. The primary contribution of this study is the provision of a centralized platform for MSMEs to plan and manage posting schedules, integrated with an innovative